1988
DOI: 10.1093/infdis/157.3.456
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Granulocytes on Brain Edema, Intracranial Pressure, and Cerebrospinal Fluid Concentrations of Lactate and Protein in Experimental Meningitis

Abstract: Brain water content (brain edema), intracranial pressure, and cerebrospinal fluid (CSF) concentrations of lactate and protein increased significantly during 24 h of experimental meningitis due to Streptococcus pneumoniae, but changes were similar in normal and neutropenic rabbits. In sterile meningitis induced by N-formyl-methionyl-leucyl-phenylalanine (fMLP), low and high doses of fMLP were equally effective in inducing CSF pleocytosis, whereas only high doses of fMLP caused brain edema. High doses of fMLP in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 52 publications
2
44
2
Order By: Relevance
“…The results obtained with the gp91 Ϫ/Ϫ animals are in line with the results of previous studies on the role of granulocytes in the pathogenesis of pneumococcal meningitis. Thus, bacterial growth and final titers in CSF were only marginally higher in rabbits rendered leukopenic than in normal rabbits (6,30). Although pneumococci are sensitive to the bactericidal effects of ROS (24) and granulocytes from animals with pneumococcal meningitis are known to generate ROS (2), several factors can explain why these ROS are not able to effectively control pneumococcal growth in the CSF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained with the gp91 Ϫ/Ϫ animals are in line with the results of previous studies on the role of granulocytes in the pathogenesis of pneumococcal meningitis. Thus, bacterial growth and final titers in CSF were only marginally higher in rabbits rendered leukopenic than in normal rabbits (6,30). Although pneumococci are sensitive to the bactericidal effects of ROS (24) and granulocytes from animals with pneumococcal meningitis are known to generate ROS (2), several factors can explain why these ROS are not able to effectively control pneumococcal growth in the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-micrometer-thick coronal sections of formaldehyde-fixed, paraffin-embedded brain tissue at the level of the hippocampus and third ventricle were stained with hematoxylin and eosin and investigated by light microscopy for five animals per group. Images were captured with OpenLab (Improvision, Coventry, United Kingdom) by using a digital camera (Hamamatsu, Photonics, Hamamatsu, Japan) and were scored for the extent of inflammatory infiltrate (Ͼ90% of which was neutrophilic granulocytes [30]) by using NIH Image. Subarachnoid inflammation was determined by measuring the area occupied by infiltrating cells in the subarachnoid space covering the area of (i) the retrosplenial motor cortex or (ii) the perirhinal cortex over a length of 850 m by using the density slicing procedure (4).…”
Section: Animals Gp91mentioning
confidence: 99%
“…The model of experimental meningitis in rabbits, originally described by Dacey and Sande [19], was modified to allow the study of pathophysiologic parameters [9,22]. New Zealand white rabbits weighing 2-3 kg were anesthetized intravenously with 30 mg of pentobarbitol/kg (Nembutal; Abbott, Cham, Switzerland) and a helmet formed with dental acrylic was attached to the skull by four screws.…”
Section: Model Of Experimentalmeningitismentioning
confidence: 99%
“…To study the pathogenesis of bacterial meningitis, animal models of this disease have been developed. It has been shown that certain bacterial virulence factors as well as host immune responses are important in the induction phase and progression of this disease (3). It is believed that exacerbation of meningitis is due to increased levels of proinflammatory cytokines, partly a consequence of antibiotic therapy leading to disruption of bacterial cell walls, resulting in the local release of biologically active cell wall products such as LPS.…”
mentioning
confidence: 99%